Analysis Of Entrepreneurial Interest In College Students - Hardiyono, Hardiyono; Zirait, Muhammad Akif; Nursyafaat, Muhammad (Jurnal Mirai Management, 2022)
This study aims to analyze the factors that influence entrepreneurial interest among STIE AMKOP Makassar students, focusing on variables such as intrinsic and extrinsic motivation, attitudes towards risk, and environmental influences. The results of this research are expected to provide valuable insights for the development of entrepreneurship education and training programs, as well as contribute to the academic literature on entrepreneurship in Indonesia. The research method used is a quantitative approach by distributing questionnaires to students, which aims to measure aspects related to entrepreneurial interest. Research findings show that intrinsic motivation, such as personal satisfaction and self-achievement, as well as extrinsic factors such as income potential and social support, have a significant effect on entrepreneurial interest. In addition, attitudes towards environmental risks and influences also play an important role in shaping this interest. This research has limitations in terms of scope and generalization of results, but is expected to contribute to supporting the development of entrepreneurship among the younger generation in Indonesia. Keywords: Entrepreneurial Motivation, Attitude to Risk, Environmental Influences